2013
DOI: 10.1103/physrevd.87.104003
|View full text |Cite
|
Sign up to set email alerts
|

Systematic biases in parameter estimation of binary black-hole mergers

Abstract: Parameter estimation of binary-black-hole merger events in gravitational-wave data relies on matched-filtering techniques, which, in turn, depend on accurate model waveforms. Here we characterize the systematic biases introduced in measuring astrophysical parameters of binary black holes by applying the currently most accurate effective-one-body templates to simulated data containing non-spinning numerical-relativity waveforms. For advanced ground-based detectors, we find that the systematic biases are well wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(101 citation statements)
references
References 128 publications
(207 reference statements)
5
95
1
Order By: Relevance
“…Those coefficients have been denoted adjustable or flexible parameters. In particular, EOB non-spinning waveforms (including the first four subdominant modes) have been developed with any mass ratio and shown to be indistinguishable from highly-accurate NR waveforms with mass ratios 1-6 up to SNRs of ∼ 50 [355]. Note, however, that current NR waveforms cover the full detector bandwidth only for binaries with total mass larger than M > ∼ 100M , thus those results are not yet conclusive.…”
Section: Interface Between Theory and Observationsmentioning
confidence: 79%
“…Those coefficients have been denoted adjustable or flexible parameters. In particular, EOB non-spinning waveforms (including the first four subdominant modes) have been developed with any mass ratio and shown to be indistinguishable from highly-accurate NR waveforms with mass ratios 1-6 up to SNRs of ∼ 50 [355]. Note, however, that current NR waveforms cover the full detector bandwidth only for binaries with total mass larger than M > ∼ 100M , thus those results are not yet conclusive.…”
Section: Interface Between Theory and Observationsmentioning
confidence: 79%
“…We included only the dominant l = m = 2 mode of the gravitational wave signal in our simulations, as this is the only mode included in the SEOBNRv2 reduced order model. This omission means that our results can only serve as a conservative estimate of the parameter estimation performance for IMBHB systems, since the higher frequency harmonics of the signal can carry information to further constrain the signal model, especially at high masses [40][41][42]. Further development of ROMs to include both higher harmonics and spin is necessary to provide timely results with the best possible accuracy.…”
Section: Simulationsmentioning
confidence: 99%
“…In Ref. [89], it was shown that for events with SNR<50 (applicable for LIGO), any bias in characterizing the GW events, introduced by the use of current waveforms, remains within the relevant statistical errors associated with the widths of the posterior distribution functions. More recently, in [90], it was also shown that even if the location on the sky and the distance to the binary are well known, either using an electromagnetic counterpart signal, or in the future by previous observations of the system [91] with eLISA [92], the accuracy in measuring the spins and masses of the binary BHs does not improve significantly.…”
Section: Figmentioning
confidence: 99%